2001
DOI: 10.1021/la010171x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of a Cationic Polyelectrolyte on Escherichia coli Bacteria:  2. Interactions between the Bacterial Surfaces Covered with the Polymer

Abstract: Quaternized polyvinylpyridine (PVPQ) was used as a cationic polymer to destabilize an Escherichia coli bacterial suspension. The optical density and the fraction of free cells, obtained by light scattering measurements, were recorded as a function of the introduced polymer amount, as a way to monitor the stability of the suspension. The flocculation was almost complete for polymer dosages ranging from about 28 to 47 mg of carbon of PVPQ per dry g of bacteria. These dosages correspond to still negatively charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…The dilute (OD 600 $ 0.1) clusters contain a smaller proportion of bacteria, and some bacteria are free or in small aggregates. The moderately sized clusters formed under such conditions, with a large excess of nanoparticles, suggest the presence of mild deflocculation of the bacteria, similar to observations of colloid restabilization at high polymer concentration in previous studies of molecular chitosan, 5,14,15 and molecular polyvinylpyridine 33 as aggregation agents. Further experiments performed at even higher chitosan nanoparticle concentrations will indicate whether the nanoparticle concentration behavior diverges from classical flocculation theory, 33 or whether the concentration range examined here is too limited for significant deflocculation to occur.…”
Section: Effect Of Bacterial Concentration On Bacteria Clusteringsupporting
confidence: 85%
See 1 more Smart Citation
“…The dilute (OD 600 $ 0.1) clusters contain a smaller proportion of bacteria, and some bacteria are free or in small aggregates. The moderately sized clusters formed under such conditions, with a large excess of nanoparticles, suggest the presence of mild deflocculation of the bacteria, similar to observations of colloid restabilization at high polymer concentration in previous studies of molecular chitosan, 5,14,15 and molecular polyvinylpyridine 33 as aggregation agents. Further experiments performed at even higher chitosan nanoparticle concentrations will indicate whether the nanoparticle concentration behavior diverges from classical flocculation theory, 33 or whether the concentration range examined here is too limited for significant deflocculation to occur.…”
Section: Effect Of Bacterial Concentration On Bacteria Clusteringsupporting
confidence: 85%
“…For example, Châtellier et al were the first to study the impact of a cationic polymer, polyvinylpyridine, on the stability of an E. coli suspension, and found that the bacteria flocculation is highly dependent on the polymer concentration. 33 Pearson et al found that a characteristic zeta potential can be used as a measure of optimal flocculation of different fermentation broth systems, and is independent of the added polymer dose, concentration, and dosing method. 34 An interesting question that this study begins to address is how well the predictions of classical flocculation theory describe the behavior of nanoparticle flocculants.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be remembered that bacterial adhesion is not always only driven by first-order electrostatic interactions. The architecture of charge heterogeneities on the bacterial surfaces can be significant, and it can lead to attractive interactions even between negatively charged surfaces (e.g., Châtellier et al 2001;Walker et al 2005).…”
Section: Effect Of Growth Phase and Metabolic Activity On Adhesionmentioning
confidence: 99%
“…The aggregation of bacteria with polyelectrolytes is a crucial stage in many water treatment operations and biotechnological processes [1][2][3][4]. The intrinsic complexity of the microorganisms, their diversity, their intricate biointerphasial features (presence/absence and nature of their extracellular polymeric substances), make it difficult to assess the interaction mechanisms between the polyelectrolyte and the biocolloids.…”
Section: -Introductionmentioning
confidence: 99%